Novel Roles of the Picornaviral 3D Polymerase in Viral Pathogenesis - Jason Kerkvliet; Ramakrishna Edukulla; Moses Rodriguez (Advances in Virology)
The RNA-dependent RNA-polymerase, 3Dpol, is an essential component in the picornavirus genome for the replication of single stranded RNA. However, transgenic expression of 3Dpol in mice has antiviral effects. Here, we discuss the structure and function of 3Dpol during picornavirus replication, we review the evidence and consequence of a host immune response to epitopes in 3Dpol after picornavirus infection, highlight data showing the antiviral effects of transgenic 3Dpol from Theiler's murine encephalomyelitis virus (TMEV), and discuss potential mechanisms by which 3Dpol is causing this antiviral effect in mice.